TANGGUNG JAWAB HUKUM RUMAH SAKIT DALAM KASUS MALPRAKTIK MEDIS: PERSPEKTIF UU NO. 17 TAHUN 2023 TENTANG KESEHATAN - Harry, Andreas; Widjaja, Gunawan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This article discusses the legal liability of hospitals in cases of medical malpractice based on Law No. 17 of 2023 concerning Health. This law provides a clear legal framework regarding the obligation of hospitals to ensure that all medical procedures performed are in accordance with applicable professional standards. In the event of malpractice, the hospital may be subject to civil liability to provide compensation to the victim as well as criminal liability if there is evidence of negligence or gross violations. In addition, Law No. 17 of 2023 emphasizes the patient's right to obtain safe and quality medical services, with a structured complaint and dispute resolution mechanism, as well as supervision and sanctions for violations. Thus, this law is designed to improve the quality of health services and strengthen patient protection from the risk of medical malpractice.